CONTRASTIVE ANALYSIS BETWEEN ENGLISH AND INDONESIAN SUFFIXES IN “THE RAINBOW TROOPS” NOVEL - Yuni Nur Alifah; Budi Susatyo; Dholiful Hadi (Universitas PGRI Ronggolawe Tuban, 2024)
This study aims to know the Contrastive Analysis Between English And Indonesian Suffixes In “The Rainbow Troops” Novel. This study was design in content analysis qualitative research because the object of the study was a novel. Moreover, as the data was in the form of words and field notes, so the data were analysed qualitatively. The researcher also conducted the analysis used contrastive analysis to more focus on differences and similarities of English and Indonesian suffixes. The instrument used to collect the data is the form of checklist. Based on the background of the case above, this study is conducted to analyze kinds of English and Indonesian suffixes and also analyze differences and similarities between English and Indonesian suffixes The result of this study showed in term on kinds of English and Indonesian suffixes are: a. Noun (-acne, -ence, -er, -or, -ist, -ian, -tion, -tion, -ness, ion, -ing, -ment, -ity, -ism, -dom, -ship, -ent, -ary, -ure, -tude, -hood, -eer, logy, -age, -ant); b. Verb (-ize/-ise, -ate, -ify, -en); c. Adverb (-ly) and; d. Adjective (al, -ar, -ic, -ical, -able/-ible, -ous, -ful, -less, -ish, -ed, -ive, -er, -ate,-ent, est). As for the Indonesian suffixes there are: a. Noun (-an, -is, -isasi, -isme, -itas, -wan/wati, -man); b. Verb (-an, -i, -kan); c. Adjective (-an, -al, -if, -is, -i, -iah). The result about the differences and similarities of suffixes between English and Indonesian suffixes in “The Rainbow Troops” Novel are: first the difference in English suffixes, the researcher only find any adverb (-ly, lovely, politely, wisely, etc). As for the Indonesian suffixes in “Laskar Pelangi” is nominal which include: (-an, jutaan, ribuan ratusan, etc). The similarities of suffixes English and Indonesian have three similarities, there are: Noun, Adjective and Verb.